Acetyl-Leucine slows disease progression in lysosomal storage disorders - Kaya, E; Smith, DA; Smith, C; Morris, L; Fineran, P; Morten, KJ; Poulton, J; Frances Platt (Oxford University Press, 2020)
Acetyl-DL-leucine is a derivative of the branched chain amino acid leucine. In observational clinical studies acetyl-DL-leucine improved symptoms of ataxia, in particular in patients with the lysosomal storage disorder, Niemann-Pick disease type C1. Here, we investigated acetyl-DL-leucine and its enantiomers acetyl-L-leucine and acetyl-D-leucine in symptomatic Npc1-/- mice and observed improvement in ataxia with both individual enantiomers and acetyl-DL-leucine. When acetyl-DL-leucine and acetyl-L-leucine were administered pre-symptomatically to Npc1-/- mice, both treatments delayed disease progression and extended life span, whereas acetyl-D-leucine did not. These data are consistent with acetyl-L-leucine being the neuroprotective enantiomer. Altered glucose and antioxidant metabolism were implicated as one of the potential mechanisms of action of the L enantiomer in Npc1-/- mice. When the standard of care drug miglustat and acetyl-DL-leucine were used in combination significant synergy resulted. In agreement with these pre-clinical data, when Niemann-Pick disease type C1 patients were evaluated after 12 months of acetyl-DL-leucine treatment, rates of disease progression were slowed, with stabilisation or improvement in multiple neurological domains. A beneficial effect of acetyl-DL-leucine on gait was also observed in this study in a mouse model of GM2 gangliosidosis (Sandhoff disease) and in Tay-Sachs and Sandhoff disease patients in individual cases of off-label-use. Taken together, we have identified an unanticipated neuroprotective effect of acetyl-L-leucine and underlying mechanisms of action in lysosomal storage diseases, supporting its further evaluation in clinical trials in lysosomal disorders.